Management strategies of potentially resectable colorectal liver metastases in a cohort of Bangladeshi patients (BIRDEM Medical Journal, 2019)
Background: Colorectal cancer with liver metastases (CRLM) is stage IV disease. Only 60% patients present with palpable liver or a liver mass and at laparotomy 80% hepatic metastases can be detected. Synchronous CRLM (SCRRLM) is indicative of poor prognosis than metachronous (MCRLM) counterpart. Only 13-15% of SCLM are eligible for curative resection. Surgical intervention offers long term cure with overall survival in 37-58% patients. This study was designed to validate different approaches of management to patients with CRLM in Bangladeshi patients.Methods: In this prospective observational study, we observed different management approaches in 41 Bangladeshi individuals with CRLM from January 2010 to January 2018 in different tertiary care hospitals of Dhaka. They were thoroughly evaluated and prepared for surgical resection. After detection both synchronous and metachronous CRLM, patients were treated surgically with colonic resection and liver resection with simultaneous approach, lesion first approach, liver first approach. Intraoperative ultrasound was valuable in localization of liver lesions. Patients were followed up for a minimum 6 months to maximum period of 61 months.Results: The study included 41 patients between ages of 21 to 70 years, of them 22 (53.65%) males and 19 (46.34%) were female. Among them, 19 patients (46.34%) had synchronous lesion and 22 (53.66%) had metachronous lesion. Neoadjuvant therapy was given in 9 (21.95%) patients. All the patients received adjuvant therapy. Multiple metastetectomy was done in 31 (75.60%) patients. In our series, following margin negative hepatic resection,14 (34.14%) patients survived 3 years and 3(7.31 %) patients survived 5 years.Conclusion: CRLM signifies an advanced disease at presentation. Hepatic resection following resection of colorectal primary is curative. Simultaneous liver with colonic resection is safe and effective in cases of small hepatic metastases.Birdem Med J 2019; 9(3): 207-212